Implementation of the Reading to Learn Learning Method in Improving Ability Read Poetry Student Class V - Pertiwi, Satria; Yessi Fitriani; Muhammad Ali (Global Action and Education for Society, 2025)
Study This aiming to: (1) Know ability read poetry student Class V of SDN 14 Sembawa through implementation method reading to learn learning; (2) Knowing the magnitude percentage improvement ability read poetry student Class V of SDN 14 Sembawa through implementation method reading to learn learning. Type of research This is study actions carried out in 2 cycles and each cycle consists of from two meetings with allocation time every 2x35 minute meeting. Research This carried out in class V of SDN 14 Sembawa Regency Banyuasin. Data collection techniques are carried out through reading test activity poetry. Research results This show that: (1) Through implementation method reading to learn skills student Class V of SDN 14 Sembawa read poetry can increase; (2) The size percentage improvement ability student Class V of SDN 14 Sembawa read poetry from cycle I to cycle to II is 8.94%.